Kearifan Lokal Dalam Tradisi Upacara Adat Pada Masyarakat Desa Jalawastu - Intan Nur Hasanah; Faniya Al Ferina; Alhimmah Aurastanasarif Syahar; Sinta Sinta; Didik Tri Setiyoko (Mathematics Education Study Program, 2025)
Local wisdom really upholds the term tradition. There are many types of traditions, including songs, dances, and even traditional ceremonies. Traditional ceremonies are a type of local wisdom that needs to be preserved and maintained. Traditional ceremonies are a form of gratitude from the people to the creator for being given food or an abundant harvest. There are many traditional ceremonies required, including marriage ceremonies, birth ceremonies and death ceremonies. In this article the traditional ceremony discussed is the Ngasa traditional ceremony. The traditional ngasa ceremony is a ceremony carried out by the Jalawastu village community. This ceremony is held once a year, namely on Tuesday Kliwon. The people of Jalawastu village wear white clothes and perform rituals of gratitude to the creator.